SIFAT MACHIAVELLIAN, ORIENTASI ETIS, EQUITY SENSITIIVITY DAN BUDAYA JAWA TERHADAP PERILAKU ETIS DENGAN INDEPENDENSI SEBAGAI VARIABEL INTERVENING - Titis Puspitaningrum Dewi Kartika (Universitas Muhammadiyah Malang)
This study would like to examine the influences on Machiavellian characteristic, Equity Sensitivity, and Javanese Culture to Ethical Behavior as the intervening variable. Sample used in this study was auditor at KAP in Surabaya. This study also used path analysis for technique data analysis.The result of reliable and validity test showed that the questionnaire is reliable, while the validity demonstrated that from 91 total question items, 28 items are not valid. The result of this study indicated that auditor with high Machiavelliancharacter will tend to behave independently is unproven. However, it is proven that auditors with high Machiavelliancharacter will tend to behave unethically. Auditor with Machiavelliancharacter who has an effect on ethical behavior followed by independent attitude as intervening variable is unproven.The hypothesis that auditor with high level of independency will tend to influence ethical behavior is unproven. Ethical orientation influenced on ethical behavior is unproven. It is proven that Equity Sensitivity influenced on ethical behavior. In addition, the hypothesis that Javanese Cultur has an effect on ethical behavior is proven. Consequently, independency could not be proven as intervening variable which influences between Machiavellian character to Ethical Behavior. Ke ywords: Ethical Orientation, Equity Sensitivity, Javanese Culture, Ethical Behavior, Independency, Machiavellian